PERSEPSI SUPERVISOR LAPANGAN TERHADAP KESIAPAN MAHASISWAJURUSAN TEKNIK SIPIL FT UNP DALAM MELAKSANAKAN PLI - 1206-1221 , Tauri Eldara (Universitas Negeri Padang, 2016)
ABSTRACT This study aims to reveal about the readiness of students majoring in civil engineering faculty of engineering of UNP in 2015 period in implementing the Industrial Field Experience, which is viewed from the aspect of cognitive, affective, and psychomotor aspects.This research is quantitative descriptive with a population of 59 supervisors from 9 companies where the Civil Engineering students of Padang University implementingthe Field Experience Industry (PLI) in 2015 in the city of Padang. The sample in this study were 37 supervisors by using the random sampling techniques.The data were collected by using questionnaires. From the research, it was found the perception of supervisor of the readiness of students of Department of Civil Engineering, Faculty of Engineering, University of Padang, in implementing the PLI in Padang is ready for affective and less prepared for cognitive and psychomotor aspects. The final judging from the overall aspect that the perception of field supervisors toward students of Civil Engineering FT-UNP in implementing the PLI in Padang are less prepared.Keywords: Perception, Readiness, PLI.